Pengaruh Likuiditas dan Profitabilitas terhadap Harga Saham pada Perusahaan Manufaktur Tekstil dan Garmen - Salsabila, Anindiya; Adiza, Tengku Narasiya; Sulistyani, Alfira; Gaol, Perawati Lumban; Laia, Insaf (Jurnal Ekonomi & Bisnis, 2025)
Liquidity and profitability are two important aspects in assessing a company’s financial performance. Liquidity reflects the company's ability to meet its short-term obligations, while profitability indicates the company’s efficiency in generating profit. Investors tend to consider both factors before making investment decisions. A good level of liquidity and profitability can enhance investor confidence, which positively affects stock demand and ultimately influences stock price movements in the market. This is particularly relevant in the textile and garment manufacturing sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The purpose of this study is to understand the relationship between these variables and stock prices, especially in facing economic challenges such as the COVID-19 pandemic. The population used includes all textile and garment sector manufacturing companies listed on the IDX from 2019 to 2022. The research method uses a quantitative approach, with samples selected using purposive sampling. From a total of 22 companies, only 10 were selected. The data analysis techniques used include descriptive statistics tests, classical assumption tests, and hypothesis testing, with the assistance of SPSS 25 for Windows. The results of hypothesis testing on stock prices indicate that liquidity and profitability variables do not have a significant effect on stock prices. The R-square value is 0.67, indicating that 67% of the variables in this study affect stock prices, while the remaining 33% are influenced by other variables outside this research. The contribution of this research indicates that investors do not need to consider liquidity and profitability when investing, particularly in the textile and garment industry sector.